Isolation of Potential Anti-Gout Compound from Burdock Root and Synthesis of Vanillin Derivatives Using Pharmacophore Modelling and Biological Evaluation - Sam Ezekiel, Radhakrishnan (Universiti Malaysia Sarawak (UNIMAS), 2021)
Nature plays an important role by being the source of medicinal agent leading towards the relief of pain or treatment of several diseases through traditional medicine using plants where it is being adopted by modern developed countries in surge of discovering new novel potent compounds as a therapeutic agent. This is due to the phytochemical properties of the chemical compounds found in each plant. Arctium lappa is well known as burdock has been used as an herb due to its various healing properties where it has the tendency to treat hypertension, inflammation disorder, and many more including treating gout. The phenolic components of the burdock root play a very important role in these healing properties. Furthermore, vanillin is a well-known ingredient all around the world used as flavoring substance is also being used for pharmacological benefit due to its various biological activity. Gout affects mostly the elderly person due to the changes in diet and long-life expectations. This leads to the build-up of uric acid in the blood where the major enzyme involves in the conversion of uric acid is a xanthine oxidase. Therefore, this study was carried out to identify the phytochemical properties of burdock root towards inhibition of xanthine oxidase and synthesis of vanillin derivatives. The vanillin derivatives were synthesized based on the scaffold of the phenolic composition of the burdock root with the aid of pharmacophore modeling. Lastly, the in silico screening of the isolated compound and vanillin derivatives and biological evaluation based on cytotoxicity, antioxidant and enzymatic assay was carried out. Two compounds namely ethyl erucate and chlorogenic acid was successfully isolated and identified. These compounds were isolated from the fractions of dichloromethane and ethyl acetate where this partition showed good antioxidant activity and xanthine oxidase inhibition. The chlorogenic acid shows a promising inhibition toward the formation of uric acid with 64.98% at 100ug/ml whereas ethyl erucate does not inhibit the formation of uric acid. In addition, the vanillin derivatives were successfully synthesized with the screening of pharmacophore modelling. Based on the two approaches of pharmacophore modelling important features for a compound to possess in order to inhibit xanthine oxidase are hydrogen bond acceptor (HBA), negatively ionizable, and hydrophobic (Hy) in structure-based approach whereas Hy and HBA in ligand-based approach. Chlorogenic acid and vanillin derivatives have these properties which were proven in silico aspects. The vanillin derivatives were subjected to the biological evaluation assay. Six of the vanillin derivatives (compound C3, C7, C8, C9, C10, and C11) were subjected to xanthine oxidase inhibition assay due to the high toxicity and less antioxidant activity of the other vanillin derivatives. These tested vanillin derivatives showed a promising inhibition activity with 83.62%, 82.76%, 92.36%, 79.70%, 82.01%, and 74.42% respectively at 100ug/ml. Therefore, chlorogenic acid and these selected vanillin derivatives have the properties towards inhibition of xanthine oxidase via in vitro aspect.